The Pathologist's Story and the Colors - Javier Torres Gómez Francisco (Journal of Clinical and Diagnostic Pathology, 2021)
This essay reflects on the craft of diagnostic pathology, using color and pattern as a narrative lens. Through case vignettes, it illustrates how morphology, staining, and visual reasoning translate into clinical answers. The perspective emphasizes communication, uncertainty management, and the human dimension of laboratory work.